The tidal disruption event AT2017eqx: spectroscopic evolution from hydrogen rich to poor suggests an atmosphere and outflow. Issue 2 (4th July 2019) - Nicholl, M; Blanchard, P K; Berger, E; Gomez, S; Margutti, R; Alexander, K D; Guillochon, J; Leja, J; Chornock, R; Snios, B; Auchettl, K; Bruce, A G; et al.
ABSTRACT: We present and analyse a new tidal disruption event (TDE), AT2017eqx at redshift z = 0.1089, discovered by Pan-STARRS and ATLAS. The position of the transient is consistent with the nucleus of its host galaxy; the spectrum shows a persistent blackbody temperature T ≳ 20 000 K with broad H i and He ii emission; and it peaks at a blackbody luminosity of L ≈ 10 44 erg s −1 . The lines are initially centred at zero velocity, but by 100 d, the H i lines disappear while the He ii develops a blueshift of ≳ 5000 km s −1 . Both the early- and late-time morphologies have been seen in other TDEs, but the complete transition between them is unprecedented. The evolution can be explained by combining an extended atmosphere, undergoing slow contraction, with a wind in the polar direction becoming visible at late times. Our observations confirm that a lack of hydrogen a TDE spectrum does not indicate a stripped star, while the proposed model implies that much of the diversity in TDEs may be due to the observer viewing angle. Modelling the light curve suggests AT2017eqx resulted from the complete disruption of a solar-mass star by a black hole of ∼10 6.3 M⊙ . The host is another Balmer-strong absorption galaxy, though fainter and less centrally concentrated than most TDE hosts. Radio limits rule out a relativistic jet, while X-ray limits at 500 d are among the deepest for a TDE at this phase.